2022
DOI: 10.1002/chem.202201199
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Porous Poly(ionic liquid) – Organic Cage Composite Membrane for Efficient Iodine Capture

Abstract: The effective capture of iodine with high volatility and poisonousness is significant for reprocessing the spent nuclear fuel. In this article, we report a hierarchically porous poly(ionic liquid)-organic cage composite membrane (PIL@CC3) possessing a gradient content distribution of CC3 cage crystals throughout the membrane to capture iodine vapor. The introduction of microporous CC3 can significantly enhance the uptake capacity of iodine up to 980 mg g À 1 , which is superior to that of a pristine PIL membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…These thermal-responsive access and pores in SCMP are expected to achieve effective iodine capture and locking (Figure C). In addition, the pore distribution (Figure S5) showed that there was a hierarchical pore structure (micropore, mesopore, and macropore) in SCMP, which is conducive to the diffusion of gaseous molecules in the material …”
Section: Resultsmentioning
confidence: 99%
“…These thermal-responsive access and pores in SCMP are expected to achieve effective iodine capture and locking (Figure C). In addition, the pore distribution (Figure S5) showed that there was a hierarchical pore structure (micropore, mesopore, and macropore) in SCMP, which is conducive to the diffusion of gaseous molecules in the material …”
Section: Resultsmentioning
confidence: 99%
“…Aiming to elucidate the adsorption mechanism, various spectral studies were performed, which demonstrated the excellent ability for iodine capture originating from the strong interaction between adsorbed iodine species and nitrogen-rich groups. During the same year, the group utilized POC-10 to synthesize four additional cage-based COFs [87] and developed them as effective adsorbents for capturing iodine vapor.…”
Section: Gas Phase Adsorption and Separationmentioning
confidence: 99%